Memahami film / Himawan Pratista; editor, Agustinus Dwi Nugroho, Yosua Aji Febrianto; ilustrator, Eka Prasetya Hendrawan, Swa Setyawan Adinegoro - HIMAWAN PRATISTA , 1974-; Agustinus Dwi Nugroho; Yosua Aji Febrianto; Prasetyo Hendrawan; Swa Setyawan Adinegoro (Montase Press, 2017)
336 hlm. : ilus. ; 23 cm.